Controle da mamite subclínica de vacas em lactação através da antibioticoterapia - Sonia Rolim Reis (2000)
This work evaluated the effectiveness of antibiotic therapy to control subclinical mastitis in lactating cows. We treated 86 of 39 animals infected teats in three dairy farms, divided into stages of lactation from 15 to 100 days and 101 to 200 days. We applied two or three doses of 250 mg of sodium cefacetrile (cephalothin) intrammamary. The drug remained within 24 hours of the udder quarters of the treated animals. Twenty-eight of 14 animals infected teats were kept as untreated control. The groups of treated animals and controls were assessed on days 0, 14, 25 and 40 after treatment through the evidence from California Mastitis Test (CMT), somatic cell count (SCC), isolation and identification of pathogens and milk production. Among the pathogens found, Staphylococcus aureus and coagulase-negative Staphylococcus were the most common microorganisms isolated (43.14%), followed by Bacillus spp, Corynebacterium bovis, Streptococcus uberis and Escherichia coli. After 14 days of treatment there was a reduction of 61.4% of intramammary infections, as well as a marked decrease in the SCC and positive reactions to the CMT in the treatment groups in both lactation periods. Between 25 and 40 after treatment, these differences were not significant (p> 0.05). There were relapses or reinfections among treated teats. In relation to milk production was not effective gains between treated animals (p> 0.05). It can be concluded that antibiotic therapy during lactation was not effective for control of subclinical mastitis, even in animals with high somatic cell counts